Buddha, Socrates, and us : ethical living in uncertain times - Batchelor, Stephen (Yale University Press, 2025)
"In this book, Stephen Batchelor explores the philosophical, social, and political worlds of the Buddha and Socrates, showing how their teachings continue to provide lessons in how to lead a flourishing and engaged life. Keenly aware of the fickle and conflicted nature of the human mind, Gotama and Socrates inspired their followers to act with humility and courage, risk and resolve, doubt and confidence. Drawing on their insights, and those of their followers, Batchelor uncovers a middle way between Buddhist dharma and Greek philosophy that can serve as a starting point for a 'secular faith' that addresses the most pressing spiritual and planetary issues of our age"--